2021
DOI: 10.1371/journal.pone.0252456
|View full text |Cite
|
Sign up to set email alerts
|

Potential effects of GPS collars on the behaviour of two red pandas (Ailurus fulgens) in Rotterdam Zoo

Abstract: GPS collars are frequently used to study the (behavioural) ecology of species. However, such collars can cause behavioural changes and can have negative physiological effects on the individuals wearing them. A pilot study to obtain data on behavioural and physiological effects of GPS collars on the target species would therefore be recommended, especially when it concerns rare or endangered species. The red panda (Ailurus fulgens) is a small carnivore endemic to the mountains of Central Asia that is currently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Information on enclosure use was also recorded, focusing on whether the red pandas were on the ground, or if they were using elevated areas of the enclosure, such as trees and branches. The ethogram of the study is reported in Tables 1 and 2 (maternal behaviours) and was prepared based on preliminary observation of the subjects and on previous studies of the red panda [14][15][16][23][24][25][26][27]. For each subject, forty-eight 30 min sessions were carried out, for a total of 1440 min per subject (96 sessions, 2880 min per pair).…”
Section: Procedures and Data Collectionmentioning
confidence: 99%
See 3 more Smart Citations
“…Information on enclosure use was also recorded, focusing on whether the red pandas were on the ground, or if they were using elevated areas of the enclosure, such as trees and branches. The ethogram of the study is reported in Tables 1 and 2 (maternal behaviours) and was prepared based on preliminary observation of the subjects and on previous studies of the red panda [14][15][16][23][24][25][26][27]. For each subject, forty-eight 30 min sessions were carried out, for a total of 1440 min per subject (96 sessions, 2880 min per pair).…”
Section: Procedures and Data Collectionmentioning
confidence: 99%
“…Moreover, the order in which each subject was observed was counterbalanced over sessions to ensure that observation of each individual was uniformly distributed over the whole observation time. [14,16,[23][24][25][26][27].…”
Section: Procedures and Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…In captive scimitar-horned oryx Oryx dammah, Stabach et al [67] showed elevated stress hormone levels for up to 5 days and behavioral changes (e.g., increased headshaking) for up to 3 days in collared individuals. Van de Bunte [73] found that collared red pandas Ailurus fulgens in captivity reduced daily activity levels and food intake compared to non-collared individuals. In free-ranging red deer Cervus elaphus, Becciolini et al [7] found increased movement rates and avoidance of their center of activity for up to 10 days, likely reflecting recovery from effects of the deployment procedure.…”
Section: Introductionmentioning
confidence: 99%